Combination therapy application of Abemaciclib with Doxorubicin in triple negative breast cancer cell line MDA-MB-231 - Eralp, Tugce Nur; Sevinc, Akin; Mansuroglu, Banu (C M B ASSOC, 2024)
Due to lack of clinical biomarkers, Triple Negative Breast Cancer (TNBC) is more likely to have spread to other tissues at time of diagnosis and therapy planning generally involves use of cytotoxic chemotherapy agents, such as Doxorubicin. We aimed to investigate possible advantages of using combination strategy using Doxorubicin alongside Abemaciclib. After determining the IC50 values for Doxorubicin (DOX) and Abemaciclib (ABE); CompuSyn and ComBenefit software were used to reveal the effect resulting from the combination of two drugs. Following the determined effect, cell death was revealed by fluorescence microscopy and a colony forming assay was performed to see the potential of even a single cancer cell with adhesive character to survive over time and form a clone of itself. Detection of changing antioxidant activity following DOX, ABE and DOX+ABE combination therapy in MDAMB231 cells was determined by measuring MDA, SOD and GSH activities. The expression of Cleaved Caspase 3, PARP, Cleaved PARP, Cdk2 and Bax, which changed as a result of DOX, ABE and DOX+ABE application, was shown by Western Blotting.Cyclin-dependent kinase inhibitors appear as promising agents in therapy planning for breast cancer due to their prominent role in cell cycle regulation, where the number of studies interrogating its efficiency in the treatment of cancer such as TNBC is limited. For this reason, in this study, we aimed to determine the impact of the combined use of the CDK4/6 inhibitors ABE and DOX on the cytotoxicity, apoptotic homeostasis, alterations in antioxidative mechanisms, and the molecular pathways that they utilize. Our results showed that when used in combination, Doxorubicin and Abemaciclib showed a synergistic effect on TNBC cell line MDA-MB-231.
Keywords: Triple negative breast cancer; TNBC; Abemaciclib; Doxorubicin; Combination therapy; ASSAY; Biochemistry & Molecular Biology; Cell Biology